Different Numbers of Long-Pulse 1064-nm Nd-YAG Laser Treatments for Onychomycosis: A Pilot Study. (20th January 2020) - Zhang, Rui-na; Zhuo, Feng-lin; Wang, Dong-kun; Ma, Li-zhi; Zhao, Jun-ying; Li, Lin-feng
Abstract : Purpose. To examine the benefits of different numbers of 1064-nm Nd-YAG laser treatments in patients with onychomycosis. Methods . This was a pilot study of patients with onychomycosis who were divided into three groups: four treatment sessions (group A), eight sessions (group B), and 12 sessions (group C). Only infected nails of degrees II–III (Scoring Clinical Index for Onychomycosis) were included. Treatment was given once a week using a long-pulse Nd-YAG 1064-nm laser. Patients were followed at 8, 16, and 24 weeks after the first treatment. Side effects were recorded. Results . Treatments were completed for 442 nails in 102 patients. The efficacy rates at 8, 16, and 24 weeks were 35.5%, 38.7%, and 37.4% for group A; 31.4%, 41.7%, and 44.0% for group B; and 27.7%, 50.0%, and 55.4% for group C, respectively. There was a significant difference in the efficacy rate at 24 weeks (P = 0.016 ) between groups A and C, but not for groups A vs. B, or for groups B vs. C. No difference in the efficacy rate at 8 or 16 weeks was observed among the three groups. In all three groups, the efficacy was better for degree II nails than for degree III nails (all P < 0.05 ). No side effects occurred. Conclusions . The 1064-nm Nd-YAG laser had clinical benefits against onychomycosis. Higher numbers of treatments provided better long-term (24-week) benefits, but had no impact on the short-term outcomes. The efficacy of laser treatment on degree II onychomycosis was better than for degree III.